2017
DOI: 10.1016/j.jaad.2017.04.1127
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns and costs of acne/rosacea medications in Medicare patients vary by prescriber specialty

Abstract: Background Prescription patterns for acne/rosacea medications have not been described in the Medicare population, and comparisons across specialties are lacking. Objective To describe the medications used for treating acne/rosacea in the Medicare population and evaluate differences in costs between specialties. Methods A cross-sectional study was performed of the Centers for Medicare & Medicaid Services 2008/2010 Prescription Drug Profiles, containing 100% of Medicare Part D claims. Results Topical antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…16,21 Curiously, long-term low dosing of doxycycline for ocular rosacea appears to be the universally accepted practice as this strategy is believed to bypass antimicrobial resistance, but investigation into conformation of this fact with more sophisticated genomic tools is lacking. [2][3][4] We note that antibiotic susceptibility determined by culture-based techniques may not fully represent the resistance pro le. 22 Growing phenotypically resistant cultures in petri dishes only reveals the bacterial pro le grown in culture, not the complete colonization and/ or infection of a patients' sampled system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21 Curiously, long-term low dosing of doxycycline for ocular rosacea appears to be the universally accepted practice as this strategy is believed to bypass antimicrobial resistance, but investigation into conformation of this fact with more sophisticated genomic tools is lacking. [2][3][4] We note that antibiotic susceptibility determined by culture-based techniques may not fully represent the resistance pro le. 22 Growing phenotypically resistant cultures in petri dishes only reveals the bacterial pro le grown in culture, not the complete colonization and/ or infection of a patients' sampled system.…”
Section: Discussionmentioning
confidence: 99%
“…3 The most commonly used systemic treatment for rosacea is the bacteriostatic antibiotic doxycycline. 3,4 Rosacea treatment regimens of doxycycline vary widely. 6 Treatment-dose doxycycline for systemic infections is 200 mg a day.…”
mentioning
confidence: 99%
“…FPs are known to prescribe antibiotics at the highest rate compared to other specialties. 9 However, when all the prescriptions are taken into account, antibiotics prescribed by FPs for skin diseases constitute 8% of the total. 10 FPs were found to prescribe systemic antibiotics to 33-37% of AV patients during initial examination, rising to 43% at repeated examinations within 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…FPs are known to prescribe antibiotics at the highest rate compared to other specialties 9 . However, when all the prescriptions are taken into account, antibiotics prescribed by FPs for skin diseases constitute 8% of the total 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et.al, 2017 revealed that higher brand-name usage and a broader range of topical steroids prescribed by specialists than primary care, which were associated with increased costs. The most common drug class utilized was topical antibiotics, accounting for 63% of all prescriptions [77]. Acne affects a large proportion of the Canadian population and has psychosocial and financial consequences.…”
Section: Economic Burden Of Avmentioning
confidence: 99%